Pilosopiyang Pinoy: Uso Pa Ba? (The Relevance of Filipino Philosophy in Social Renewal) - Abulad, Romualdo E (Archīum Ateneo, 2019)
This paper evaluates the titular question and features a summative evaluation and critique of the works and contributions of Leonardo Mercado, Dionisio Miranda, Albert Alejo, Rolando Gripaldo (1947-2017), and Florentino Timbreza to the anthropological and cultural approaches that form a significant part of the discourses on Filipino philosophy. In this piece, Abulad maintains, as in his other writings, that any strict emphasis with regard to methodology restricts the true potential of Filipino philosophy. He buttresses this assertion by invoking postmodernism's 'incredulity towards metanarratives' We should be skeptical about the metanarrative of Filipino identity for it is precisely our rootlessness that defines us. Towards the end, he cites Emerita Quito's openness as a distinct philosophical attitude that had made her, to-date, unsurpassable. This remarkable trait, for Abulad, should inspire us to welcome the new: with the “collapse of borders and the merger of horizons,” it would serve us well to continuously rethink the role of philosophy.